Human DNA mismatch repair: coupling of mismatch recognition to strand-specific excision - Wang, Huixian (Oxford University Press, 2007)
Eukaryotic mismatch-repair (MMR) proteins MutSα and MutLα couple recognition of base mismatches to strand-specific excision, initiated in vivo at growing 3′ ends and 5′ Okazaki-fragment ends or, in human nuclear extracts, at nicks in exogenous circular substrates. We addressed five biochemical questions relevant to coupling models. Excision remained fully efficient at DNA:MutSα ratios of nearly 1 to 1 at various mismatch-nick distances, suggesting a requirement for only one MutSα molecule per substrate. As the mismatch-nick DNA contour distance D in exogenous substrates increased from 0.26 to 0.98 kbp, initiation of excision in extracts decreased as D−0.43 rather than the D−1 to D−2 predicted by some translocation or diffusion models. Virtually all excision was along the shorter (3′–5′) nick-mismatch, even when the other (5′–3′) path was less than twice as long. These observations argue against stochastically directed translocating/diffusing recognition complexes. The failure of mismatched DNA in trans to provoke excision of separate nicked homoduplexes argues against one-stage (concerted) triggering of excision initiation by recognition complexes acting through space. However, proteins associated with gapped DNA did appear to compete in trans with those in cis to mismatch-associated proteins. Thus, as in Escherichia coli, eukaryotic MMR may involve distinct initial-activation and excision-path-commitment stages.